2016
DOI: 10.1016/j.ajpath.2016.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Increased Pyruvate Dehydrogenase Kinase 4 Expression in Lung Pericytes Is Associated with Reduced Endothelial-Pericyte Interactions and Small Vessel Loss in Pulmonary Arterial Hypertension

Abstract: Reduced endothelial-pericyte interactions are linked to progressive small vessel loss in pulmonary arterial hypertension (PAH), but the molecular mechanisms underlying this disease remain poorly understood. To identify relevant gene candidates associated with aberrant pericyte behavior, we performed a transcriptome analysis of patient-derived donor control and PAH lung pericytes followed by functional genomics analysis. Compared with donor control cells, PAH pericytes had significant enrichment of genes involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 70 publications
0
34
0
Order By: Relevance
“…On the opposite spectrum, excessive pericyte proliferation promotes disease progression in pulmonary artery hypertension (PAH), hypoxia-induced retinopathies (characterized by excessive neovascularization), and kidney and liver fibrosis (Rabinovitch, 2012;Ferland-McCollough et al, 2017;Dubrac et al, 2018). Studies using pericytes derived from PAH patients indicate that aberrant pericyte proliferation and migration is fueled by glycolysis, as these cells had elevated glycolytic capacity and lower mitochondrial activity (Rabinovitch, 2012;Yuan et al, 2016). Thus, repression of pericyte glycolytic activity could provide a useful therapeutic approach in this disease.…”
Section: Correcting the Functions Of Native Pericytesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the opposite spectrum, excessive pericyte proliferation promotes disease progression in pulmonary artery hypertension (PAH), hypoxia-induced retinopathies (characterized by excessive neovascularization), and kidney and liver fibrosis (Rabinovitch, 2012;Ferland-McCollough et al, 2017;Dubrac et al, 2018). Studies using pericytes derived from PAH patients indicate that aberrant pericyte proliferation and migration is fueled by glycolysis, as these cells had elevated glycolytic capacity and lower mitochondrial activity (Rabinovitch, 2012;Yuan et al, 2016). Thus, repression of pericyte glycolytic activity could provide a useful therapeutic approach in this disease.…”
Section: Correcting the Functions Of Native Pericytesmentioning
confidence: 99%
“…Thus, repression of pericyte glycolytic activity could provide a useful therapeutic approach in this disease. Recently, siRNA-mediated knock-down of PDK4 (which suppresses mitochondrial activity in favor of glycolysis by inhibition of pyruvate dehydrogenase) was shown to increase PAH-derived pericyte mitochondrial function, lower their proliferation and improve their interactions with endothelial cells (Yuan et al, 2016), demonstrating promise of this conceptual approach. Similar strategies may be useful in regulating pericyte proliferation in chronic kidney disease or retinopathies, although these approaches remain to be tested.…”
Section: Correcting the Functions Of Native Pericytesmentioning
confidence: 99%
“…Several studies have been carried out in retinal pericytes in the context of diabetic retinopathy, but without exploring glucose metabolism in pericytes . The only work about pericyte metabolism performed to our knowledge demonstrated that lung pericytes from pulmonary arterial hypertension patients presented higher expression of PDK‐1, an inhibitor of PDH, than healthy pericytes . Therefore, it could be considered that normal pericytes display higher rates of OXPHOS than those of glycolysis.…”
Section: Metabolism Of Cells At the Tumor Microenvironmentmentioning
confidence: 99%
“…54,58,59 Hypertension has been associated with both an increase and a decrease in pericyte numbers. [60][61][62][63][64] In mice with Ang-II-induced hypertension, the number of pericytes in cerebral arteries is decreased, leading to blood-brain barrier disruption. 60 In contrast, SHR show increased pericyte number within the brain microcirculation, specifically within the motor cortex and pons.…”
Section: Pericytesmentioning
confidence: 99%